STUDI LITERATUR REVIEW: LATIHAN STRETCHING TERHADAP PENURUNAN TINGKAT NYERI PUNGGUNG BAWAH PADA LANSIA - M Imam Mustagfirin; Tri Nataliswati; Nurul Hidayah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
One of the daily physical problems that are often found in the elderly is low back pain. Low back pain symptoms range from aches to a stabbing or shooting sensation. This pain can make it difficult for sufferers to move or stand upright. One of the non-pharmacological therapies to deal with low back pain in the elderly is stretching exercises, stretching exercises are exercises that are rarely done by the community, while this exercise is easy and has been widely proven to be able to reduce the level of lower back pain in the elderly. The purpose of this study was to find out about the effect of stretching exercises on the elderly who experience low back pain in 10 journals that match the inclusion criteria. This research uses the reviewed literature. Journals that are searched nationally and internationally via Google Schoolar, Pubmed, Ebsco and Proques. Journals that were traced in 2015-2020, after the search for journals were found, they were identified and filtered to 165 after which there were 10 journals according to inclusion and exclusion criteria. Using the keywords elderly, low back pain, and stretching exercises, while in English using is ((